Chronic pancreatitis – diagnosis and treatment - Gąsiorowska, Anita; Małecka-Panas, Ewa (Przewodnik Lekarza/Guide for GPs, 2007)
Chronic pancreatitis is a chronic inflammatory condition characterized by fibrosis with destruction of the exocrine and endocrine tissue of the pancreas. Alcohol abuse is the common cause of chronic pancreatitis in western population. Approximately 20% of the causes of chronic pancreatitis are idiopathic, and remaining causes include hereditary pancreatitis, obstructive pancreatitis and autoimmune pancreatitis. Diagnosis of chronic pancreatitis is based on history and confirmed by imaging studies and laboratory tests that assess pancreatic structure and function.